Tax reforms on fiscal incentives in Ecuador and their relationship with the accounting results of small businesses in the commercial sector in Cotopaxi - Cangui Navas, Lizeth (2023)
Considering that the incorporation of tax incentives in the tax regulations allows improving the economy of a country, and are aimed at achieving various goals such as generating new sources of employment, promoting care for the environment, as well as improving the quality of life of the community, they also seek to favor companies internally by reducing income tax spending, and; therefore, generate higher profits after taxes and higher cash flows. For this reason, the objective of this research was to establish whether the tax incentives were related to the accounting results to the year 2021 in the small companies of the commercial sector of the province of Cotopaxi regulated by the Superintendency of Companies, Securities and Insurance of Ecuador. For which, a field investigation was carried out, since the data of the companies was collected physically, applying a questionnaire. It was shown that only 31% of the companies availed themselves of the incentives in force by 2021 and achieved a reduction in the payment of taxes before the tax administration, being one of the incentives most applied by the companies under study by the year 2021 hiring of personnel with disabilities that allows an additional 100% deduction of income tax. URL: https://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/1960